Variety of prenatally diagnosed congenital heart disease in 22q11.2 deletion syndrome - Lee, Mi-Young (Korean Society of Obstetrics and Gynecology; Korean Society of Contraception and Reproductive Health; Korean Society of Gynecologic Endocrinology; Korean Society of Gynecologic Endoscopy and Minimal Invasive Surgery; Korean Society of Maternal Fetal Medicine; Korean Society of Ultrasound in Obstetrics and Gynecology; Korean Urogynecologic Society, 2014)
OBJECTIVE: To analyze the spectrum of prenatally diagnosed congenital heart disease in a Korean population with 22q11.2 deletion syndrome, and to provide guidelines for screening 22q11.2 deletion prenatally. METHODS: This retrospective study evaluated 1,137 consecutive fetuses that had prenatal genetic testing for 22q11.2 deletion because of suspected congenital heart disease between September 2002 and December 2012, at Asan Medical Center, Seoul, Korea. RESULTS: Main cardiovascular diseases in the 53 fetuses with confirmed 22q11.2 deletions were tetralogy of Fallot (n = 24, 45%), interrupted aortic arch (n = 10, 19%), ventricular septal defect (n = 5, 9%), double outlet right ventricle (n = 4, 8%), and coarctation of the aorta (n = 4, 8%). Other cardiac defects were rarely associated with 22q11.2 deletion. One fetus had persistent truncus arteriosus, one had aortic stenosis, and one had hypoplastic right heart syndrome. Two fetuses had normal intracardiac anatomy with an isolated right aortic arch, and one had an isolated bilateral superior vena cava. CONCLUSION: A variety of congenital heart diseases were seen during the prenatal period. Conotruncal cardiac defects except transposition of great arteries were strongly associated with 22q11.2 deletion. When such anomalies are diagnosed by fetal echocardiography, genetic testing for 22q11.2 deletion should be offered. Even if less frequent deletion-related cardiac defects are detected, other related anomalies, such as thymic hypoplasia or aplasia, should be evaluated to rule out a 22q11.2 deletion.